Pengaruh Penerapan E-Audit, Kompetensi, Dan Independensi Auditor Terhadap Kualitas Audit - Glen Lazwardi Qurba (Jurnal Riset Mahasiswa, 2020)
This study aims to determine the effect of the implementation of E-Audit based on ATLAS (Audit Tool and Linked Archived System), Competence, and Independence on Audit Quality at Public Accounting Firms in Bandung. The research method used is a quantitative method with descriptive and verification approaches. The sampling technique was carried out by purposive sampling method which resulted in 9 public accounting firms and 54 auditors. The data analysis method of this research is multiple regression analysis, classical assumption test, correlation analysis and the coefficient of determination. While the hypothesis testing used is the partial test statistical method (t test) and simultaneous test (F test) using SPSS 24. Based on the results obtained, it shows that the application of E-Audit, Competence, and Independence has a positive effect and simultaneously gives an effect of 67 , 4% on the quality of the audit.